2017
DOI: 10.1017/s1431927617012685
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Excited Optical Luminescence and Portable Electron Probe Microanalyzer–Cathodoluminescence (EPMA–CL) Analyzers for On-Line and On-Site Analysis of Nonmetallic Inclusions in Steel

Abstract: The potential of the application of an X-ray excited optical luminescence (XEOL) analyzer and portable analyzers, composed of a cathodoluminescence (CL) spectrometer and electron probe microanalyzer (EPMA), to the on-line and on-site analysis of nonmetallic inclusions in steel is investigated as the first step leading to their practical use. MgAl2O4 spinel and Al2O3 particles were identified by capturing the luminescence as a result of irradiating X-rays in air on a model sample containing MgAl2O4 spinel and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Therefore, the XEOL analysis is a promising approach for an online analysis of nonmetallic inclusions in steel. In our previous paper, Al 2 O 3 reagent particles emitted blue luminescence . In contrast, we have also reported that Al 2 O 3 inclusions in steels emit red or blue luminescence owing to the difference in the concentrations of impurities in the Al 2 O 3 inclusions, observed by a cathodoluminescence (CL) analysis, where the same phenomenon as that in the XEOL analysis is observed with an incident electron beam instead of an X‐ray.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Therefore, the XEOL analysis is a promising approach for an online analysis of nonmetallic inclusions in steel. In our previous paper, Al 2 O 3 reagent particles emitted blue luminescence . In contrast, we have also reported that Al 2 O 3 inclusions in steels emit red or blue luminescence owing to the difference in the concentrations of impurities in the Al 2 O 3 inclusions, observed by a cathodoluminescence (CL) analysis, where the same phenomenon as that in the XEOL analysis is observed with an incident electron beam instead of an X‐ray.…”
Section: Introductionmentioning
confidence: 76%
“…In our previous paper, Al 2 O 3 reagent particles emitted blue luminescence. [16] In contrast, we have also reported that Al 2 O 3 inclusions in steels emit red or blue luminescence owing to the difference in the concentrations of impurities in the Al 2 O 3 inclusions, observed by a cathodoluminescence (CL) analysis, [17] where the same phenomenon as that in the XEOL analysis is observed with an incident electron beam instead of an X-ray. Therefore, it is necessary to perform an XEOL analysis for samples prepared under conditions similar to those in the industrial steel production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration voltage of the STEM was set to 200 kV. The CL images and spectra were acquired using a custom SEM-CL system, whose details have been previously reported (Imashuku et al, 2017a(Imashuku et al, , 2017b(Imashuku et al, , 2017cImashuku & Wagatsuma, 2018, 2019a, 2019b, 2019c, 2020c, 2020dTsuneda et al, 2019). In brief, the CL images were captured through a quartz viewport attached to the SEM (Mighty-8DXL, TECHNEX, Tokyo, Japan) by a digital mirrorless camera (α7RII, Sony Corp., Tokyo, Japan) equipped with a zoom lens (LZH-10A-05T, Seimitu Wave Inc., Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, these methods cannot simultaneously identify the composition, size, shape, and amount of inclusions. We have recently demonstrated that capturing cathodoluminescence (CL) images enables MgAl 2 O 4 spinel and Al 2 O 3 inclusions in steels to be distinguished more rapidly than by the conventional method . CL analysis is obtaining images and spectra based on the phenomenon of light emission from materials as a result of electron bombardment and can simultaneously identify the amount, size distribution, shape, and occasionally, composition of non‐metallic inclusions in steel …”
Section: Introductionmentioning
confidence: 99%